Role of Early Tendon Transfers in Radial Nerve Palsy - S. D. Pandey; Pramod Kumar; Ramesh Chandra; Arun Kumar Singh (Indian Journal of Plastic Surgery)
Sixteen cases of wrist drop were managed by tendon transfers using Boyes Technique for early rehabilitation. The procedure was found useful both in remedial and irremedial radial nerve lesions. In the former they act as internal splints during the period of recovery. Results in high as well as in low radial nerve lesion were equally good. Patients were able to return to their original work, 6 to 8 weeks after surgery.